Impact of financial stress in advanced and emerging economies - Valerio Roncagliolo, Flavio César (2022)
Purpose: The purpose of the paper is to examine the differences in the impact of financial stress in advanced and emerging economies. Design/methodology/approach: The authors employ a panel vector autoregression model (PVAR) for a comparative analysis of the relationship between financial stress, economic growth and monetary stability in 14 advanced and emerging economies. A homogeneous measure of financial stress is constructed and measured as an index that provides signals of stress episodes in an economy. Findings: The impact of financial stress shocks is greater on the economic growth of advanced economies; likewise, financial stress shocks are significant only in advanced economies. The interbank interest rate is negatively affected by financial stress in emerging economies. In general, the results show a clear view of the importance of financial stability and the economic relevance of financial stress measures in the context of macro-prudential regulation. Originality/value: The results can be extended to monetary policy to implement measures that mitigate the impact of future financial crises.